2021
DOI: 10.1186/s12955-021-01705-z
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life and self-reported cognitive function in patients with delayed neurocognitive recovery after radical prostatectomy: a prospective follow-up study

Abstract: Background Delayed neurocognitive recovery (DNCR) is a common and serious complication after radical prostatectomy. We hypothesized that patients with DNCR in the early postoperative period would report reduced health-related quality of life (HRQoL) and more cognitive failures 12 months after surgery, compared with patients without DNCR. Methods We performed a 12-month follow-up on 367 patients who had been enrolled in a prospective observational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…In recent years, dNCR has attracted attention because it causes economic and medical burdens, reduces quality of life, increases morbidity, and causes early mortality [ 4 , 5 ]. dNCR can have a long-term impact on patients’ daily lives by impairing memory, attention, activity, and perception [ 6 ]. Unfortunately, because the pathological mechanisms underlying dNCR have not been completely elucidated, there are presently no effective preventive or therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, dNCR has attracted attention because it causes economic and medical burdens, reduces quality of life, increases morbidity, and causes early mortality [ 4 , 5 ]. dNCR can have a long-term impact on patients’ daily lives by impairing memory, attention, activity, and perception [ 6 ]. Unfortunately, because the pathological mechanisms underlying dNCR have not been completely elucidated, there are presently no effective preventive or therapeutic strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the evidence based on normal and diverse clinical samples supports the connection of EF with QoL as well as with psychological wellbeing in terms of emotional and social adjustment [19][20][21][22][23]. Presently, the studies are focusing on age related decline in EF and QoL in healthy aging adults on one hand [15], and on the EF-QoL link in healthy and clinical samples on the other hand [21,23]. However, evidence for the link between EF and QoL is lacking for samples of illicit substance abusers.…”
Section: Associations Between Age Ef and Qolmentioning
confidence: 98%
“…Yet, currently, there is little evidence regarding the association of EF with QoL in substance abuser population. Nonetheless, the evidence based on normal and diverse clinical samples supports the connection of EF with QoL as well as with psychological wellbeing in terms of emotional and social adjustment [19][20][21][22][23]. Presently, the studies are focusing on age related decline in EF and QoL in healthy aging adults on one hand [15], and on the EF-QoL link in healthy and clinical samples on the other hand [21,23].…”
Section: Associations Between Age Ef and Qolmentioning
confidence: 99%
“…28 A recent study reported that those with delayed neurocognitive recovery between 3 and 5 days after surgery had more self-reported cognitive impairment in memory, attention, action, and perception at 12 month after radical prostatectomy. 29 It seems that patients with POCD have even worse outcomes. For example, studies found that patients with POCD at 3 months after surgery had twice the proportion of new impairment in activities of daily living when compared with those without 30 ; they also had a higher risk of long-term mortality.…”
Section: Delayed Neurocognitive Recovery and Pocdmentioning
confidence: 99%
“…For example, patients with cognitive decline 1 week after surgery are more likely to leave the labor market and depend on social transfer payment 28 . A recent study reported that those with delayed neurocognitive recovery between 3 and 5 days after surgery had more self‐reported cognitive impairment in memory, attention, action, and perception at 12 month after radical prostatectomy 29 . It seems that patients with POCD have even worse outcomes.…”
Section: Epidemiology and Outcomes Of Perioperative Ncdsmentioning
confidence: 99%